Unveiling Monoterpene Biosynthesis in Taiwania cryptomerioides via Functional Characterization - Li-Ting Ma (MDPI AG, 2021)
Taiwania cryptomerioides is a monotypic species, and its terpenoid-rich property has been reported in recent years. To uncover monoterpene biosynthesis in T. cryptomerioides, this study used transcriptome mining to identify candidates with tentative monoterpene synthase activity. Along with the phylogenetic analysis and in vitro assay, two geraniol synthases (TcTPS13 and TcTPS14), a linalool synthase (TcTPS15), and a β-pinene synthase (TcTPS16), were functionally characterized. Via the comparison of catalytic residues, the Cys/Ser at region 1 might be crucial in determining the formation of α-pinene or β-pinene. In addition, the Cupressaceae monoterpene synthases were phylogenetically clustered together; they are unique and different from those of published conifer species. In summary, this study aimed to uncover the ambiguous monoterpenoid network in T. cryptomerioide, which would expand the landscape of monoterpene biosynthesis in Cupressaceae species.